Estimates for first exit times of non-Markovian Ito processes - Dokuchaev, Nikolai (Taylor & Francis, 2008)
First exit times and their path-wise dependence on trajectories are studied for non-Markovian Itô processes. Estimates of distances between two exit times are obtained. In particular, it follows that first exit times of two Itô processes are close if their trajectories are close.